Just listen equality and diversity - Jay, David; Alpha Film.; West Sulffolk College (Bristol, United Kingdom : Classroom Video Ltd)
'The people interviewed in the programme talk frankly about their experiences and the problems they encounter. The interviews look at the prejudices people have, the stereotypes that have been created and where such opinions come from. Fact or fiction? Each interviewee also talks about how they would like society to change'--Container.
DVD format.
System requirements : progressive scan DVD player.
Keywords: Minorities; Prejudices -- Religious aspects